Contemporary Trends in Hospital Admissions and Outcomes in Patients With Critical Limb Ischemia: An Analysis From the National Inpatient Sample Database. Issue 2 (February 2021) - Anantha-Narayanan, Mahesh; Doshi, Rajkumar P.; Patel, Krunalkumar; Sheikh, Azfar Bilal; Llanos-Chea, Fiorella; Abbott, Jinnette Dawn; Shishehbor, Mehdi H.; Guzman, Raul J.; Hiatt, William R.; Duval, Sue; Mena-Hurtado, Carlos; Smolderen, Kim G.
Abstract : Background: Critical limb ischemia (CLI) morbidity and mortality rates have historically been disproportionately higher than for other atherosclerotic diseases, however, recent trends have not been reported. In patients admitted with CLI, we aimed to examine trends in in-hospital mortality, major amputations, length of stay, and cost of hospitalizations overall and stratified by type of revascularization procedures. Methods: Using 2011 to 2017 National Inpatient Sample data, we identified CLI-related admissions based on International Classification of Diseases, Ninth and Tenth Edition, Clinical Modification codes. Primary outcomes of interest were in-hospital mortality and major amputations. Secondary outcomes were the length of stay and cost of hospitalization. We stratified outcomes based on endovascular or open surgical interventions. We also performed hierarchical multivariable regression analyses of outcomes based on age, sex, race, hospital size, type, and location. Results: We identified 2 643 087 CLI-related admissions between 2011 and 2017. CLI admissions increased from 0.9% to 1.4% P trend <0.0001 as well as overall peripheral artery disease admissions (4.5%–8.9%, P trend <0.0001). In-hospital mortality for the entire CLI cohort decreased from 3.3% to 2.7%, P trend <0.0001, and major amputations decreased from 10.9% to 7%, P trend <0.0001. A decline was also noted for the length of stay from 5.7 (3.1–10.1) to 5.4 (3.0–9.2) days ( P trend <0.0001), whereas admission costs increased from USD $11 791 ($6676–$21 712) to $12 597 ($7248–$22 748; P trend <0.0001). Endovascular interventions increased ( P trend <0.0001) against a decline in surgical interventions ( P trend <0.0001). Black race, female sex, and age ≥60 years were associated with higher in-hospital mortality, whereas Black race, male sex, and age<60 years were associated with higher major amputations. Conclusions: A relatively small decrease in absolute numbers for mortality and major amputations were observed against a backdrop of increasing CLI admissions over recent years. Patients with CLI received more endovascular interventions than surgical interventions over time. However, admissions for endovascular interventions were characterized by higher risk patient profiles and a higher risk of major amputations as compared with surgical interventions. Abstract : Supplemental Digital Content is available in the text.